Analysis of In-Situ Stress and Well Trajectory in Carbonate and Sandstone Reservoirs. A Case Study of Mishrif and Zubair Formations in the West Qurna Oilfield, Southern Iraq - Al-Dujaili, Ahmed N. (Iraqi Journal of Science, 2025)
Reservoir Geomechanics plays a crucial role in maximizing the efficiency of the drilling process, guaranteeing accurate placement of horizontal wells, and accomplishing effective well completion. Accurately determining the levels of pore pressure and the vertical, minimum, and maximum horizontal stresses is a crucial component of thorough geomechanical modeling. Mishrif carbonate reservoir in the Middle Cretaceous and Zubair sandstone reservoir in the Lower Cretaceous are the essential reservoirs in the West Qurna oilfield, southern Iraq. This study aims to analyse the best Well trajectory conditions in the carbonate and sandstone reservoirs using many correlations for thirteen wells (that were drilled from 2014 to 2016) in the West Qurna/1 field. The findings indicate that the geomechanical problems in Mishrif wells are less severe compared to Zubair wells concerning optimizing pore pressure and the presence of geo-pressurized shale sequence. In addition, Mishrif wells in the eastern flank of the oilfield are less prone to drilling mud loss problems than the western flank. All the wells drilled towards maximum horizontal stress showed minimal wellbore stability problems in which the best average maximum horizontal stress direction is 55 +/- 20 and 235 +/-20 deg. Mishrif wells are less sensitive to azimuth and deviation than Zubair wells. On the other hand, Zubair wells are more sensitive to inclination. The maximum horizontal stress direction is recommendable to reduce Well complexity and challenging drilling environment. To establish the drilling window during drilling operations in the West Qurna 1 field, it is necessary to have a formation prediction that takes into account lithology and anticipated wellbore stability pressures.